1998
DOI: 10.1080/026782998206713
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic donor-acceptor twin molecules with covalently linked sheet-like pentaalkyne and nitrofluorenone sub-units

Abstract: Charge-transfer (CT ) twin mesogens are presented which consist of sheet-like pentayne donor moieties with di erent peripheral substituents chemically linked with nitro substituted uorenone sub-units via¯exible alkyl spacers. A novel plastic rectangular columnar (Colrp) phase is reported for the laterally unsubstituted member of the pentayne based CT twins. The phase is characterized by a three-dimensional crystal-like correlation of ordered columns in a rectangular lattice, while the molecular sub-units are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(10 reference statements)
2
6
0
Order By: Relevance
“…The polar diagram of the diffraction efficiency is displayed as an insert. It has a shape which corresponds roughly to the one reported by us for other liquid crystalline materials. ,,
1 (a and b) Holographic growth curve of compounds 1 and 2 (the nonzero diffraction efficiency at t = 0 results from the background noise originating from the optical setup). (c and d) Holographic growth curve of the doped compounds with TNF.
…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The polar diagram of the diffraction efficiency is displayed as an insert. It has a shape which corresponds roughly to the one reported by us for other liquid crystalline materials. ,,
1 (a and b) Holographic growth curve of compounds 1 and 2 (the nonzero diffraction efficiency at t = 0 results from the background noise originating from the optical setup). (c and d) Holographic growth curve of the doped compounds with TNF.
…”
Section: Resultssupporting
confidence: 64%
“…The role of the liquid crystalline environment has turned out to be two-fold: it provides a stabilization of the induced orientational order even at temperatures above the glass-transition temperature, and it results in a strong amplification of the optical response. This has become obvious from the observation of a gain effect for materials which could be frozen-in into an amorphous state and became liquid crystalline only on annealing at elevated temperatures. The storage performed in the amorphous state gave rise to weak optical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of columnar mesophases from covalently linked donor−acceptor mesogens has been studied, in particular, by Wendorff and Janietz et al, who synthesized, e.g., complexes of electron-rich pentaalkynylbenzene attached directly to TNF. , In these systems strong intermolecular donor−acceptor interactions lead to the formation of highly ordered, columnar mesophases. In further studies elaborating on this work a calamitic azobenzene spacer was used to connect pentaalkynylbenzene or triphenylene ( 197 , Figure ) to TNF.…”
Section: 22 Covalent Donor−acceptor Liquid Crystalsmentioning
confidence: 99%
“…Two pentakis[(4-alkylphenyl)ethynyl]benzene derivatives (DLC-1 and DLC-2) were employed here to elucidate orientational behavior of the DLCs spin-cast on the film of 1 , which was obliquely irradiated, accompanied by annealing in advance. Polarized microscope observations revealed that DLC-1 and DLC-2 showed a N D phase in the range of 172−215 and 66−84 °C, respectively.…”
mentioning
confidence: 99%